Kebijakan Pengelolaan Lingkungan Hidup dalam Prespektif Pendidikan Sains Islam - Thoriq Al Qubais (ANNAHDLIYAH: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to examine the concept of nature conservation in an Islamic perspective through a literature study approach. Nature conservation in Islam is seen as part of worship, which emphasizes the balance between environmental utilization and conservation. Through literature research, it was found that Islam places humans as caliphs on earth who are responsible for preserving nature. The Qur'an strongly condemns acts of environmental destruction and emphasizes that there will be retribution for the perpetrators. Thus, preserving the environment is a moral and spiritual obligation inherent in Islamic teachings.